Wondering about God together : research-led learning & teaching in theological education - Learning and Teaching Theology Conference (2017 : Sydney College of Divinity); Ball, L. J. (Leslie J.); Bolt, Peter G. (Macquarie Park, NSW : SCD Press, 2018)
A collection of essays originally delivered at the Sydney College of Divinity 2017 Learning & Teaching Theology Conference exploring Research-Led Theological Education.
Part 3: Academic Freedom in Theological Education -- Academic Freedom in the Thought-Policed University: Challenges for Christian Educators Today / Barry Spurr -- Exploring the Nexus between Academic Freedom and Ecclesial Expectations / Dean Smith and Rob Fringer -- The Perils of Academic Freedom: the Australian College of Theology as an Australian University of Specialisation / Geoff Treloar -- Part 4: Pedagogical Approaches to Deep Learning -- Windows, Mirrors and Icons as Ways into the Context, Content and Call of Sacred Narratives / Debra Snoddy -- In My Father s House: the Place of Wonder in Proverbs Vision of Education / A. J. Culp -- Text and Interpretation: from Classical Music to Biblical Studies / Sarah Hart -- The Pedagogy of Biblical Fiction: Where Research and Creativity Collide / Ben Chenoweth -- Is the God of the Bible an Ugly Bully? Helping Bible Students Come to Terms with Violence in the Biblical Text / Andrew Jaensch -- An Approach for Deep Theological Learning in Research Methodologies / Denise Goodwin -- The Relational Teacher: Sharing Life as Vocational Essence / Darren Cronshaw -- Deep Learning from a Shallow Surface? Encouraging Good Research in the Internet Age / Peter Bolt -- Making Good Practice Affordable: Understanding your Students with Learning Analytics / Martin Olmos -- Theological Education in Context: Exploring the Delivery of Theological Education in a Multi-Cultural Setting / Bruce Allder -- Integrating Theology in a Questioning Age / Les Ball -- Curiosity and Doubt in Researching the Future: The Contribution of Flipped Learning to Sociality in Theological Innovation / Steve Taylor and Rosemary Dewerse -- Epilogue / Peter Bolt.
Includes bibliographical references.
Keywords: Theology -- Methodology -- Congresses -- Australia; Theology -- Study and teaching -- Congresses; Research -- Methodology -- Congresses; Theology -- Australia -- Methodology -- Congresses; Australian